Improving Legal Literacy in Village Communities through a Citizens' Rights and Obligations Education Program - Dadi Waluyo; Sumardi (LPPM Akademi Teknik Adikarya, 2025)
Abstract The low level of legal literacy in rural communities often leads to various social problems, such as inter-resident conflicts, rights violations, and low community participation in the village development process. This community service program aims to improve community understanding of the rights and obligations of citizens through participatory and applicable legal outreach activities. The implementation method includes identifying community needs, developing outreach materials, and implementing legal education through interactive lectures, group discussions, and simple case simulations relevant to village life. The activities also include the distribution of educational modules as a medium for continuous learning. Evaluation of the activities was carried out through pre- and post-tests to measure improvements in participant understanding, as well as participatory observation during the activities. The results of the activities showed an increase in community understanding of the rights and obligations of citizens, particularly regarding compliance with the law, conflict resolution through deliberation, and awareness of the importance of participation in village development. In addition, the community demonstrated increased awareness in accessing legal services and government administration correctly. This program has had a positive impact on increasing legal awareness and strengthening the relationship between the community and village officials in creating an orderly and harmonious social order. Thus, a village-based legal counseling program can be an effective legal empowerment model to improve the quality of social life in a sustainable manner.